Desmopressin as a Hemostatic Agent to Provide a Dry Intraoperative Field in Rhinoplasty. Issue 5 (May 2015) - Gruber, Ronald P.; Zeidler, Kamakshi R.; Berkowitz, R. Laurence
<x xml:space="preserve">Abstract</x> Background: Intraoperative bleeding during rhinoplasty makes it difficult to sculpt cartilages. Residual blood from a wet field can lead to induration, fibrosis, and definition loss. Recent studies with desmopressin (1-deamino-8-D-arginine vasopressin) to reduce blood loss in a variety of operations and minimize postoperative bleeding problems suggest using that drug routinely for elective rhinoplasty and not just for patients with coagulation issues. Method: Seventy-three consecutive rhinoplasty patients received desmopressin for the purpose of obtaining a dry operative field. The initial dose was 0.1 μg/kg. If the field was not as dry as desired, a second dose was given; if necessary, a third dose to a maximum of 0.3 μg/kg was given. All cases exhibited a satisfactorily dry field. There were no adverse effects. A retrospective comparison was made to 300 consecutive cases not receiving desmopressin. Results: Thirty of the 73 patients received a starting dose of 0.1 μg/kg and nothing more. Fourteen received a second dose of 0.1 μg/kg because the field was not as dry as desired and 29 received a third dose of 0.1 μg/kg because the field was not as dry as desired. All 73 patients exhibited a satisfactorily dry field, in contrast to 9 percent in the group not receiving desmopressin. Conclusions: This study confirms the hemostatic effectiveness of desmopressin at lower than normally used doses in rhinoplasty. It also confirms its safety. It suggests its use in other procedures. A larger, carefully controlled study is indicated. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.